NEOLOGISMS IN THE UZBEK LANGUAGE AND THEIR TRENDS OF EMERGENCE IN THE CORPUS - Shaxzoda NORMAMATOVA; S.B.Xamdamova (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article analyzes the emergence of neologisms in modern written Uzbek, their lexical and semantic characteristics, and their frequency of usage based on corpus linguistics.